2005
DOI: 10.1073/pnas.0500729102
|View full text |Cite
|
Sign up to set email alerts
|

On the conservative nature of intragenic recombination

Abstract: Intragenic recombination rapidly creates protein sequence diversity compared with random mutation, but little is known about the relative effects of recombination and mutation on protein function. Here, we compare recombination of the distantly related ␤-lactamases PSE-4 and TEM-1 to mutation of PSE-4. We show that, among ␤-lactamase variants containing the same number of amino acid substitutions, variants created by recombination retain function with a significantly higher probability than those generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
106
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 40 publications
10
106
0
Order By: Relevance
“…An initial study showed that crossover of two encoding sequences is an effective way of producing a new encoding sequence, suggesting that local sequence patterns are important for determining whether the full protein sequence can fold to a unique structure [324]. This theoretical prediction is consistent with subsequent experiments on b-lactamase indicating that for a given number of amino acid substitutions, recombined variants are much more likely to retain function than variants generated by random point mutations [339]. In another simulation study, evolutionary dynamics that admits both point mutations and recombination leads to a much higher concentration of population in the prototype sequence than if evolution proceeds via point mutations alone, suggesting a significant role of recombination in the prototype-like behaviours of natural proteins [152].…”
Section: Predictions and Rationalizationssupporting
confidence: 69%
“…An initial study showed that crossover of two encoding sequences is an effective way of producing a new encoding sequence, suggesting that local sequence patterns are important for determining whether the full protein sequence can fold to a unique structure [324]. This theoretical prediction is consistent with subsequent experiments on b-lactamase indicating that for a given number of amino acid substitutions, recombined variants are much more likely to retain function than variants generated by random point mutations [339]. In another simulation study, evolutionary dynamics that admits both point mutations and recombination leads to a much higher concentration of population in the prototype sequence than if evolution proceeds via point mutations alone, suggesting a significant role of recombination in the prototype-like behaviours of natural proteins [152].…”
Section: Predictions and Rationalizationssupporting
confidence: 69%
“…Chimeric protein libraries are particularly desirable training sets because they uniformly sample a massive combinatorial space of mutations. In addition, the sequences within chimera libraries have a high probability of functioning (35) and display significant functional diversity (16,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although less diverse than the maximally informative chimeras, the single-block swap chimeras still contain on average 15 mutations compared with the closest parent. This is a significant amount of diversity to introduce while still maintaining localization, given that even a single mutation can destroy a protein's ability to fold or function (22).…”
Section: Resultsmentioning
confidence: 99%
“…SCHEMA recombination offers a systematic method for modular, rational diversity generation that conserves the protein's native structure and function but allows for large changes in sequence (20)(21)(22). SCHEMA divides structurally similar parent proteins into blocks that, when recombined, minimize the libraryaverage disruption of tertiary protein structure (10).…”
mentioning
confidence: 99%